Silencing of XB130 is associated with both the prognosis and chemosensitivity of gastric cancer. - Min Shi; Weizhen Huang; Li Lin; Dayong Zheng; Qiang Zuo; Lin Wang; Nina Wang; Yajun Wu; Yulin Liao; Wangjun Liao (PLoS ONE, 2012)
XB130 is a newly characterized adaptor protein that was reported to promote thyroid tumor growth, but its role in the progression of other kinds of cancer such as gastric cancer (GC) remains unknown. Accordingly, we investigated the association between XB130 expression and the prognosis of GC patients. The subjects were 411 patients with GC in stages I to IV. XB130 expression was examined in surgical specimens of GC. Kaplan-Meier analysis and the Cox proportional hazards model were used to assess the prognostic significance of XB130 for survival and recurrence. Moreover, GC cells stably transfected with XB130 short hairpin RNA were established to analyze the effect of XB130 on sensitivity of chemotherapy. The results show that both XB130 mRNA and protein expression were detectable in normal gastric tissues. The overall survival time of stage IV patients and the disease-free period after radical resection of GC in stage I-III patients were significantly shorter when immunohistochemical staining for XB130 was low than when staining was high (both p<0.05). XB130 expression also predicted tumor sensitivity to several chemotherapy agents. Viability of both XB130-silenced SGC7901 cells and wild-type cells was suppressed by 5-fluorouracil (5-FU), cisplatin, and irinotecan in a dose-dependent way, but cisplatin and irinotecan were more sensitive against sXB130-silenced GC cells and 5-FU showed higher sensitivity to wild-type cells. When treated by 5-FU, patients with high expression of XB130 tumors had a higher survival rate than those with low expression tumors. These findings indicate that reduced XB130 protein expression is a prognostic biomarker for shorter survival and a higher recurrence rate in patients with GC, as well as for the response to chemotherapy.